High concentrations of crude glycerin on ruminal parameters, microbial yield, and in vitro greenhouse gases production in dairy cows - van Cleef, E. H. C. B. [UNESP]; Sancanari, J. B. D. [UNESP]; Silva, Z. F. [UNESP]; D'Aurea, A. P. [UNESP]; Favaro, V. R. [UNESP]; van Cleef, F. O. S. [UNESP]; Homem Junior, A. C. [UNESP]; Ezequiel, J. M. B. [UNESP] (Canadian Science Publishing, Nrc Research Press, 2016)
Holstein cows were used to evaluate the inclusion of elevated concentrations of crude glycerin on ruminal parameters, production of greenhouse gases, and microbial yield. The use of up to 300 g kg(-1) reduces ruminal bacteria yield and NH3-N, without affecting the pH. Moreover, 300 g kg(-1) glycerin increases methane production.
Keywords: bacteria; glycerol; dairy cow; methane; microorganism